THE HEALTH OF WOMEN OF FERTILE AGE - Yuldasheva F. U.; Eshonkhodjaeva M. O.; Khojieva K. L.; Aliyev D. O.; Ashurov S. R. (American Journals, 2024)
The health of women of fertile age is a key aspect of their overall well-being and ability to care for future generations. It is important to support women's health during this period of life as it impacts their reproductive health and the health and well-being of their unborn children.
Keywords: Reproductivee age, fertility, demography, maternal health, women's health.